Higher Education Institution Management Strategies for Developing Citizenship of University Student - Laosawatdikul, Phatsayakorn; Charoenkul, Nuntarat; Siribanpitak, Pruet (Scholar: Human Sciences, 2016)
The objectives of this research were 1) to study the current and desirable states of management for developing citizenship of university students 2) to analyze strengths, weaknesses, opportunities and threats of management for developing citizenship of university students and 3) to develop management strategies for developing citizenship of university students. The study applied a mixed method approach. The sample population were 94 higher education institutions. The instruments used in this study were questionnaires and the strategic evaluation form to testify feasibility and appropriateness of the strategies. The data were analyzed by frequency, percentage, standard deviation, PNIModified and content analysis. The research results showed that 1) In general, the current state of management for developing citizenship of university students was performed at the middle level. While considering each aspect, democratic knowledge had the highest average ( = 3.041). The desirable state of management for developing citizenship of university students was performed at a high level as a whole. While considering each aspect, democratic knowledge had the highest average ( = 4.454). 2) The strengths of management for developing citizenship of university students were democratic participation and democratic knowledge, while the weakness of management for developing citizenship of university students was democratic skills. The opportunity for management for developing citizenship of university students was technology. While the threats of management for developing citizenship of university students were the government policy, economy and society. 3) The management strategies for developing citizenship of university students comprised (1) reforming higher education institution management for developing democratic skills of university students, (2) reforming higher education institution management for developing democratic participation of university students and (3) reforming higher education institution management for developing democratic knowledge of university students.